Prevention of Stroke in Patients With Atrial Fibrillation - Moukabary, Talal (J Atr Fibrillation, 2011)
The presence of atrial fibrillation (AF) increases the risk of stroke, especially in patients with risk factors as outlined by the CHADS2 and CHA2DS2-VASc scoring systems. Although warfarin can reduce stroke rates by over 65%, only 55% of patients, in the USA, who should be on warfarin for AF and stroke prevention are taking the drug due to the need of INR monitoring, difficulties in maintaining a therapeutic INR in the therapeutic range and dietary and drug interactions. Dabigatran, an oral direct thrombin inhibitor and rivaroxaban and apixaban, factor Xa inhibitors, have demonstrated efficacy in reducing stroke in large clinical trials. These novel anticoagulants will change the therapeutic landscape since patients will be able to prevent stroke with a lower risk of intracranial hemorrhage and without the need for INR monitoring and less drug-dietary interactions.